Experimental analysis for stabbing resistance of different aramid composite architectures. (15th January 2019) - Rodríguez-Millán, M.; Díaz-Álvarez, A.; Aranda-Ruiz, J.; Díaz-Álvarez, J.; Loya, J.A.
Abstract: Stab resistance is a crucial material property in the case of fabrics used in personal protection equipment due to the extensive occurrence of this threat. Personal Protection Equipments (PPE) are commonly based on woven aramids, where the stacking sequence is critical to improve the ratio between protection and weight. PPE should combine optimal penetration resistance with ergonomic requirements. This paper focuses on experimental characterisation of the stab protective efficiency of different architectures of aramid laminates. The influence of different stacking sequences, based on the combination of not treated (N) and thermoplastic aramids (TP), is analysed showing a significant influence of this factor. In the range of the impact energies analysed in this work, it can be concluded that the TP-N-TP sequence is the best choice for stabbing protection.